In Vitro Selection of Fab Fragments by mRNA Display and Gene-Linking Emulsion PCR - Sumida, Takeshi; Yanagawa, Hiroshi; Doi, Nobuhide (Journal of Nucleic Acids, 2012)
In vitro selection by display methods has been an effective tool for engineering recombinant antibodies. mRNA display based on a cell-free translation system has the advantages of larger library sizes and quicker selection procedures compared with cell-based display methods such as phage display. However, mRNA display has been limited to select single-chain polypeptides such as scFvs due to its characteristic of linking a nascent polypeptide with its encoding mRNA on the ribosome. Here we demonstrated a new way of selecting heterodimeric Fab fragments by using mRNA display combined with emulsion PCR. We designed a pair of complementary 5′ UTR sequences that can link the Fab heavy and light chain genes together by overlap-extension PCR in water-in-oil emulsions. We confirmed that two mRNA-displayed polypeptides for heavy and light chain of a model Fab fragment were associated into the active form and that a specific Fab fragment gene was enriched over 100-fold per round of a model affinity selection followed by the gene-linking emulsion PCR. We further performed directed evolution of Fab fragments with higher binding activity from a randomized Fab fragment library.